KEBERADAAN KARANG DI PERAIRAN PULAU NASI ACEH BESAR - Sarong, M. Ali; Artika, Wiwit; Iswadi, Iswadi; Huda, Ismul (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2025)
Corals are a type of aquatic biota inhabiting benthic environments, comprising diverse species with varying levels of presence. This research aimed to assess the number of species and the presence levels of coral species in the waters of Nasi Island, Pulau Aceh Subdistrict, Aceh Besar Regency. The research activities were conducted from July to August 2024. The methodology employed was a survey method. Data collection was carried out using a purposive sampling technique. The research area was segmented into three locations based on their geographical positions. Within each location, two observation stations were established. Each station consisted of ten research plots with dimensions of 2 m x 2 m. The number of coral species was analyzed descriptively, while the presence levels of coral species were analyzed using a presence index. The results of the study indicated that 35 coral species were found in the waters of Nasi Island, with the presence index ranging from 33.33% to 100%. Therefore, it can be concluded that the number of coral species in the waters of Nasi Island is considerably high, and the presence levels of coral species are highly variable, ranging from very rare to very abundant. Keywords :corals, Nasi Island, presence index